Silver Ions Caused Faster Diffusive Dynamics of Histone-Like Nucleoid-Structuring Proteins in Live Bacteria - Sadoon, Asmaa A. (Appl Environ Microbiol, 2020)
The antimicrobial activity and mechanism of silver ions (Ag(+)) have gained broad attention in recent years. However, dynamic studies are rare in this field. Here, we report our measurement of the effects of Ag(+) ions on the dynamics of histone-like nucleoid-structuring (H-NS) proteins in live bacteria using single-particle-tracking photoactivated localization microscopy (sptPALM). It was found that treating the bacteria with Ag(+) ions led to faster diffusive dynamics of H-NS proteins. Several techniques were used to understand the mechanism of the observed faster dynamics. Electrophoretic mobility shift assay on purified H-NS proteins indicated that Ag(+) ions weaken the binding between H-NS proteins and DNA. Isothermal titration calorimetry confirmed that DNA and Ag(+) ions interact directly. Our recently developed sensing method based on bent DNA suggested that Ag(+) ions caused dehybridization of double-stranded DNA (i.e., dissociation into single strands). These evidences led us to a plausible mechanism for the observed faster dynamics of H-NS proteins in live bacteria when subjected to Ag(+) ions: Ag(+)-induced DNA dehybridization weakens the binding between H-NS proteins and DNA. This work highlighted the importance of dynamic study of single proteins in live cells for understanding the functions of antimicrobial agents in bacteria. IMPORTANCE As so-called “superbug” bacteria resistant to commonly prescribed antibiotics have become a global threat to public health in recent years, noble metals, such as silver, in various forms have been attracting broad attention due to their antimicrobial activities. However, most of the studies in the existing literature have relied on the traditional bioassays for studying the antimicrobial mechanism of silver; in addition, temporal resolution is largely missing for understanding the effects of silver on the molecular dynamics inside bacteria. Here, we report our study of the antimicrobial effect of silver ions at the nanoscale on the diffusive dynamics of histone-like nucleoid-structuring (H-NS) proteins in live bacteria using single-particle-tracking photoactivated localization microscopy. This work highlights the importance of dynamic study of single proteins in live cells for understanding the functions of antimicrobial agents in bacteria.